1993
DOI: 10.1002/hep.1840180522
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen free radical production mediated by cocaine and its ethanol-derived metabolite, cocaethylene, in rat hepatocytes

Abstract: Cocaine ethyl ester ("cocaethylene") is a cocaine metabolite formed by hepatic carboxylesterases in the presence of ethanol. In the human liver, this pharmacologically active cocaine analog may reach concentrations similar to those of cocaine. To further investigate the intrinsic hepatotoxic potential of cocaethylene and to compare its effects with the known hepatocyte-damaging effects of cocaine, primary short-term cultures of hepatocytes derived from phenobarbital-pretreated rats were exposed to cocaine or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…route is one of the main routes used by human cocaine addicts. Having a high degree of solubility and a low ionization rate, cocaine is easily absorbed and, once in the circulation, is quickly metabolized by the liver, producing metabolites and reactive oxygen species that are responsible for its toxicity [7,21]. The present results indicate that cocaine does not induce increased frequencies of PCEMN in bone marrow cells of this mouse strain and therefore should not be assumed to have a mutagenic potential under these bioassay conditions.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…route is one of the main routes used by human cocaine addicts. Having a high degree of solubility and a low ionization rate, cocaine is easily absorbed and, once in the circulation, is quickly metabolized by the liver, producing metabolites and reactive oxygen species that are responsible for its toxicity [7,21]. The present results indicate that cocaine does not induce increased frequencies of PCEMN in bone marrow cells of this mouse strain and therefore should not be assumed to have a mutagenic potential under these bioassay conditions.…”
Section: Discussionmentioning
confidence: 58%
“…In humans, the liver morphological and biochemical effects induced by cocaine are quite similar to mice [26,27]. The oxidative stress, which seems to be one of the mechanisms associated with cocaine toxicity [7], could play a role in the liver carcinogenesis process, similar to that exerted by peroxisome proliferators [32]. It is interesting that the peroxisome proliferator and non-genotoxic hepatocarcinogen di-(2-ethyllhexyl)phthalate shares a common structure biophore with cocaine [9].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…First, it has been suggested that the nitrosonium ion, generated during the oxidation of norcocaine, or other as yet unidentified reactive metabolites, bind covalently to cellular macromolecules. However, the same authors, investigating mechanisms of cocaine toxicity in hepatocyte cultures, proved the key role of ROS but suggested that their generation occurred through nonperoxidative mechanisms [38,39]. The litera-ture studies investigating the role of ROS that lead to oxidative stress are contradictory.…”
Section: Role Of Oxidative Metabolism In Cocaine-induced Oxidative Stmentioning
confidence: 99%
“…Alcohol appeared to potentiate cocaine hepatotoxicity in both humans and mice [64]. [39] suggested that the increased amount of ROS, generated during the interaction of cocaine and cocaethylene with cytochrome P 450 is responsible for intensified cocaine liver injury. The hepatotoxic implications of cocaethylene in humans have not been fully described.…”
Section: Cocaine-induced Hepatotoxicity In Humansmentioning
confidence: 99%